Casablanca - Wallis, Hal B.; Curtiz, Michael (USA: Warner Brothers [production company] ; Kuala Lumpur : Berjaya HVN Sdn. Bhd. [distributor])
Casablanca: an easy city to enter, but a much harder one to leave, especially if your name is on the Nazis' most wanted list. And heading that list is Czech Resistance leader Victor Laszio, whose only hope is Rick Blaine, a cynical American who sticks his neck out for no one..especially Victor's wife, Lisa, the ex-lover who broke, his heart
n.2 is acquisition for KPI (Kelab Pencinta Ilmu)
Cast: Humprey Bogart, Ingrid Bergman, Paul Henreid
Keywords: Communism and motion pictures; Historical films; Love in motion pictures